2022
DOI: 10.1111/ene.15265
|View full text |Cite
|
Sign up to set email alerts
|

Comparing humoral immune response to SARS‐CoV2 vaccines in people with multiple sclerosis and healthy controls: An Austrian prospective multicenter cohort study

Abstract: Background and purpose: SARS-CoV2 vaccination is recommended for patients with multiple sclerosis (pwMS), but response may be limited by disease-modifying-treatments (DMTs). The aim of this study was to compare the rates of humoral immune response and safety of SARS-CoV-2 vaccines in pwMS and healthy controls (HCs). Methods:In this multicenter prospective study on 456 pwMS and 116 HCs, SARS-CoV-2-IgG response was measured 3 months after the first vaccine dose. The primary endpoint was defined as proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
14
0
2
Order By: Relevance
“…Some authors reported a better vaccine response in pwMS on anti-CD20 treatment who did not have a complete B-cell depletion at vaccination, and there was a better response in pwMS treated with S1P modulators in the presence of a high lymphocyte count [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported a better vaccine response in pwMS on anti-CD20 treatment who did not have a complete B-cell depletion at vaccination, and there was a better response in pwMS treated with S1P modulators in the presence of a high lymphocyte count [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Literature data reported no relevant effect on vaccine response for DMDs other than anti-CD 20 and fingolimod [ 33 , 34 , 37 ]. Although anti-CD20 tend to increase the risk of severe COVID-19, and both anti-CD20 and S1P-modulators weaken the vaccine response, these drugs are precious arms against MS, and undertreatment leads to the risk of disability accrual.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a multicenter (Departments of Neurology of Medical Universities Vienna, Innsbruck and Linz) prospective observational study including 292 pwMS and 45 HC, who had all received two vaccinations during the original study (first immunization), which was originally described elsewhere ( Bsteh et al., 2022c ). PwMS were first subgrouped according to DMT status at the time of first immunization.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with multiple sclerosis (pwMS) are most commonly treated with disease-modifying therapies (DMT) that interfere with the immune system, potentially limiting immune response to vaccination and the extent of protection achieved but not altering the adverse effect profile. Several studies have shown that the humoral response to SARS-CoV-2 vaccines is not reduced in pwMS when treated with DMT other than sphingosine-1-phosphate receptor modulators (S1PMs) and anti-CD20 monoclonal antibodies (mAbs) ( Bsteh et al., 2022c ; Kornek et al., 2022 ; Sormani et al., 2021 ; Achiron et al., 2021 ). Despite poor antibody response in those patients, current guidelines do advise against discontinuation of DMT for the high risk of disease reactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS)-related disability and comorbidities can increase the risk of severe coronavirus disease-2019 (COVID-19) outcomes from severe acute respiratory syndrome–related coronavirus (SARS-CoV-2) infection [ 1 ]. Also, some disease-modifying treatments (DMTs), including anti-CD20 monoclonal antibodies and sphingosine-one-phosphate (S1P) modulators, can reduce the response to anti-SARS-CoV-2 vaccination (i.e., reduced seroconversion and/or cellular response) [ [2] , [3] , [4] ], and can subsequently be responsible for more severe COVID-19 outcomes, including hospitalizations and intensive care unit admissions [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%